“A Cormorant of Libraries”: The Future-Past of Susan Howe’s “Melville’s Marginalia” - Mark Tardi (European Journal of American Studies)
In his influential essay “The Translator as the Creator of the Canon,” Jerzy Jarniewicz outlines the characteristics of what he identifies as “but two of the most interesting species” of translator, the ambassador and the legislator. Building off of Jarniewicz’s framework (while also being indebted to Sasha Colby’s concept of a “poetics of excavation”), in this essay I propose a hybrid offspring of the ambassador and legislator—the excavator—through the example of American poet Susan Howe’s work “Melville’s Marginalia,” from her 1993 book The Nonconformist’s Memorial. Megan Williams asks, “How does Susan Howe’s use of Melville… reveal literary history and history itself to be a series of choices that must be rethought and rewritten? What are these choices, and where do they leave Howe’s work for posterity?” (106). It is Howe’s relationship to posterity that is of particular interest here. Whereas Williams and others take extraordinary care to analyze “Melville’s Marginalia” as a discrete text and to avoid making broader remarks about that text’s potential relationship to Howe’s oeuvre more generally, in my essay I consider how “Melville’s Marginalia” is consistent with a sustained effort by Howe to situate herself and her work within the frame of canonical literary figures. Moreover, by offering the contrast of poets such as Don Mee Choi, Sarah Mangold, and C. D. Wright, I suggest that Howe’s efforts, in fact, reveal and solidify the expansive versatility of canonical figures—such as Melville, Dickinson, and others—even if there is a clear critical dimension.